Activation and ecological risk assessment of heavy metals in dumping sites of Dabaoshan mine, Guangdong province, China. Issue 3 (3rd April 2017) - Feng, Hong; Wu, Jialong; Guo, Yanbiao; Dai, Jun; Lu, Ying
ABSTRACT: In Dabaoshan mine, dumping sites were the largest pollution source to the local environment. This study analyzed the activation and ecological risk of heavy metals in waste materials from five dumping sites. Results indicated that the acidification of waste materials was severe at all dumping sites, and pH decreased below 3.0 at four of the five sites. There was a drastic variation in Cu, Zn, Pb, and Cd concentrations in different sites. Site A with 12915.3 mg kg −1 Pb and 7.2 mg kg −1 Cd and site C with 1936.2 mg kg −1 Cu and 5069.0 mg kg −1 Zn were severely polluted. Higher concentrations of water-soluble Cu were probably the critical constraint for local pioneer plants. A significant positive correlation was found between the concentrations of water-soluble and HOAc-extractable elements, and the regression analysis showed that, compared with Cu, Zn and Cd, Pb was more difficult to be transformed from HOAc extractable to water soluble. Concentration of water soluble metals should be an important index, same as concentration of HOAc extractable metals, in assessing ecological risks, availability, and toxicity of heavy metals. The modified ecological risk index indicated that all dumping sites had very high potential ecological risks. It is necessary to decrease the availability of heavy metals to reduce the impact of waste materials on environment.